A biomass carbon-based nitrogen quantum dot alloy catalyst and preparation method thereof
By introducing nitrogen quantum dot biomass carbon into the Pt alloy catalyst, forming a ring structure and utilizing nitrogen elements, the problem of easy aggregation of Pt alloy catalysts is solved, and a high stability and high activity nitrogen quantum dot alloy catalyst is achieved. Improved catalytic activity and electrochemical properties.
Patent Information
- Application Number
- CN202310399281.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-11
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-04-11
AI Technical Summary
The existing Pt alloy catalysts are prone to aggregation, resulting in reduced activity, making it difficult to maintain high stability and high activity.
Using a nitrogen quantum dot alloy catalyst based on biomass carbon, preventing the aggregation of platinum and nickel particles by forming a unique ring structure, using nitrogen quantum dot biomass carbon to expose more active sites, and reducing Pt through nitrogen elements Binding energy with intermediate oxides.
The stability and activity of the catalyst are improved, excessive agglomeration of metal particles is avoided, catalytic activity is enhanced, and efficient electrochemical properties are maintained during use.
Smart Images

Figure CN116565238B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fuel cell catalytic materials, and in particular to a biomass carbon-based nitrogen quantum dot alloy catalyst and a preparation method thereof. Background Art
[0002] Hydrogen energy is a green energy source with the characteristics of high efficiency, environmental protection and renewability. Proton exchange membrane fuel cells are devices that can convert hydrogen energy into electrical energy. They are currently widely used in aerospace, automotive and other fields. Among them, the membrane electrode is the core of the proton exchange membrane fuel cell. It is the main place for converting electrical energy into chemical energy. The membrane electrode is mainly composed of a proton exchange membrane, a catalyst layer, and a gas diffusion layer. The HOR reaction of hydrogen and the ORR reaction of oxygen both occur in the catalyst layer, which is mainly catalyzed by the catalyst to make them react. The commonly used catalyst is Pt / C catalyst, which has a high reaction activity. However, Pt resources are relatively scarce and costly, so the development of new high-activity catalysts is more critical. At present, the amount of Pt used is reduced by alloying transition metal M with Pt to form binary or multi-element alloy electrocatalysts. When Pt is alloyed, its d-valence band will migrate to a lower energy level. According to the d-band theory, the binding energy of the d-valence band Pt and active intermediate oxygen species (such as O*, OH* and OOH*) is closely related. The migration energy of the d-valence band can significantly reduce the binding energy of the ORR reaction, thereby improving the catalytic activity and the power generation efficiency of the membrane electrode.
[0003] However, the alloying of Pt will make the Pt particles and the alloy have a larger surface energy, which will make the catalyst more likely to aggregate. As the chemical reaction proceeds, the agglomeration of the catalyst becomes more serious, resulting in fewer exposed active sites on the catalyst, thereby reducing the catalytic activity of the catalyst. Therefore, how to provide a Pt alloy catalyst with high stability and high activity is a technical problem that urgently needs to be solved. Summary of the invention
[0004] The present application provides a nitrogen quantum dot alloy catalyst based on biomass carbon and a preparation method thereof to solve the technical problem in the prior art that Pt alloy catalysts are prone to aggregation and result in reduced activity. The present application performs special treatment on biomass materials and forms a unique ring structure, which can prevent the aggregation of platinum particles and nickel particles to the greatest extent, thereby exposing sufficient active sites and ensuring the catalytic activity of the alloy catalyst.
[0005] In the first aspect, the present application provides a nitrogen quantum dotted alloy catalyst based on biomass carbon, the raw materials of the alloy catalyst include nitrogen quantum dotted biomass carbon, platinum salt and nickel-containing solution; the mass ratio of the nitrogen quantum dotted biomass carbon, the platinum salt and the nickel-containing solution is 1:0.1~0.3:0.1~0.3.
[0006] Optionally, the raw material of the nitrogen quantum dotted biomass carbon includes biomass carbon and nitride, and the mass ratio of the biomass carbon to the nitride is 1:1-10.
[0007] Optionally, the nitride comprises a mixture of polyetherimide and 3,4-dihydroxyphenylethylamine.
[0008] Optionally, the platinum salt comprises platinum tetrachloride; and / or,
[0009] The nickel-containing solution includes at least one of nickel chloride, nickel nitrate and nickel sulfate.
[0010] In a second aspect, the present application provides a method for preparing the alloy catalyst described in the first aspect, the method comprising:
[0011] Pre-treating the fruit skin, and then heating it under a protective atmosphere until it is carbonized to obtain biomass carbon;
[0012] Adding the mixture of the nitride and anhydrous ethanol to the biomass carbon for reaction to obtain nitrogen quantum dotted biomass carbon;
[0013] Adding the platinum salt to the nitrogen quantum dotted biomass carbon, and dripping the nickel-containing solution and the sodium ethoxide solution, stirring, and then adding sodium borohydride to the mixture, and reacting to obtain a mixed slurry;
[0014] The mixed slurry is dried and then calcined in an oxygen atmosphere to obtain a biomass carbon-based nitrogen quantum dot alloy catalyst.
[0015] Optionally, the pretreatment of the fruit skin and the subsequent heating under a protective atmosphere to obtain biomass carbon specifically includes:
[0016] Selecting fruit skins, cutting them, and then soaking them in a strong alkaline solvent to obtain pretreated fruit skins;
[0017] The pretreated fruit skin is heated under a protective atmosphere until carbonized to obtain biomass carbon.
[0018] Optionally, the strong alkaline solvent includes potassium hydroxide solution and / or sodium hydroxide solution.
[0019] Optionally, the soaking time is ≥ 8h.
[0020] Optionally, the terminal temperature of the heating is 600° C. to 900° C.; and / or,
[0021] The calcination temperature is 250°C to 350°C.
[0022] Optionally, the heating rate of the calcination is 1.5 to 2.5 times the heating rate of the heating.
[0023] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0024] The embodiment of the present application provides a nitrogen quantum dotted alloy catalyst based on biomass carbon. By introducing nitrogen quantum dotted biomass carbon into the alloy catalyst of Pt and Ni and controlling the nitrogen quantum dotted biomass carbon, on the one hand, the unique ring structure of the biomass carbon in the nitrogen quantum dotted biomass carbon can be utilized to expose more hydroxyl groups, carboxyl groups and other groups on the surface of the biomass carbon and distribute them more evenly. When the metal catalyst is subsequently loaded, the catalyst will have more contact sites with the biomass carbon and distribute them more evenly, which can also avoid excessive agglomeration of metal particles. On the other hand, the introduction of nitrogen element by nitride can move the 4S valence band of Pt to a lower energy level, thereby further reducing the binding energy of Pt with the intermediate oxide, thereby enhancing the catalytic activity of the catalyst particles. At the same time, the nitrogen element can also avoid the agglomeration of the catalyst during use, thereby obtaining an alloy catalyst with high stability and high activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0027] Figure 1 A schematic diagram of a process for preparing an alloy catalyst provided in an embodiment of the present application;
[0028] Figure 2 A schematic diagram of a detailed process for preparing an alloy catalyst provided in an embodiment of the present application. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0031] The creative thinking of this application is:
[0032] At present, Pt alloy catalysts include: octahedral Pt-Cu-M ternary alloy catalyst and Pt-Au-Cu catalyst. These two catalysts have the following characteristics:
[0033] 1. The Pt-Cu-M ternary alloy catalyst is made of platinum acetylacetonate, copper acetylacetonate, and carbonyl molybdenum as raw materials, ascorbic acid as a reducing agent, hexadecyltrimethylammonium bromide as a structure directing agent, and N,N-dimethylformamide is added to prepare octahedral platinum-copper-molybdenum alloy nanoparticles under hydrothermal conditions. The advantages of this ternary alloy catalyst are: uniform size, controllable morphology, exposure of highly active crystal faces, and improved catalyst activity on the basis of effectively reducing the platinum content. The addition of molybdenum can protect the transition metal copper, slow down the corrosion and oxidation of copper, and maintain the performance of the catalyst for a longer time;
[0034] However, molybdenum oxide itself does not have a thermodynamically stable phase and cannot maintain its thermodynamic stability during long-term use, thereby achieving the purpose of protecting the catalyst. Moreover, it cannot slow down the aggregation of Pt particles and enable the catalyst to operate stably and for a long time.
[0035] 2. The Pt-Au-Cu catalyst is prepared by chemically chelating a porous carbon substrate treated with surface groups with a metal precursor and then calcining it in a simple step. The advantages of this catalyst are: the carbon substrate is modified by oxidation and nitridation, and the overall modification is relatively complete;
[0036] However, the modification is mainly carried out by high-temperature calcination under nitrogen, which does not make the carbon substrate have a high degree of nitridation. In addition, when treated at a high temperature of 700°C, the catalyst particles will aggregate to a certain extent, reducing the reaction activity of the catalyst.
[0037] Therefore, how to provide a Pt alloy catalyst with high stability and high activity is a technical problem that urgently needs to be solved.
[0038] An embodiment of the present application provides a nitrogen quantum dotted alloy catalyst based on biomass carbon, wherein the raw materials of the alloy catalyst include nitrogen quantum dotted biomass carbon, platinum salt and nickel-containing solution; the mass ratio of the nitrogen quantum dotted biomass carbon, the platinum salt and the nickel-containing solution is 1:0.1~0.3:0.1~0.3.
[0039] In the embodiments of the present application, the mass ratio of nitrogen quantum dotted biomass carbon, platinum salt and nickel-containing solution is controlled to ensure that the nitrogen quantum dotted biomass carbon can fully contact with the platinum salt and the nickel-containing solution. At the same time, the unique ring structure on the nitrogen quantum dotted biomass carbon is utilized to expose more hydroxyl groups, carboxyl groups and other groups on the surface of the biomass carbon and distribute them more evenly, so that the platinum element in the platinum salt and the nickel element in the nickel-containing solution can be fully loaded, and the distribution of the platinum element and the nickel element can be more even.
[0040] In some optional embodiments, the raw material of the nitrogen quantum dotted biomass carbon includes biomass carbon and nitride, and the mass ratio of the biomass carbon to the nitride is 1:1-10.
[0041] In the embodiments of the present application, by controlling the specific mass ratio of biomass carbon and nitride, the unique ring structure of biomass carbon can be utilized to expose more hydroxyl groups, carboxyl groups and the like on the surface of biomass carbon and distribute them more evenly, thereby facilitating the uniform distribution of nitrogen elements in the nitride on the surface of biomass carbon and facilitating the influence of nitrogen elements on platinum, thereby further reducing the binding energy of Pt with the intermediate oxide and avoiding their agglomeration.
[0042] In some optional embodiments, the nitride comprises a mixture of polyetherimide and 3,4-dihydroxyphenylethylamine.
[0043] In the embodiments of the present application, by controlling the specific composition of the nitride, the nitrogen element can be more evenly distributed on the surface of the biomass carbon through the combined action of polyetherimide and 3,4-dihydroxyphenylethylamine, thereby facilitating the effect of the nitrogen element on platinum, thereby further reducing the binding energy between Pt and the intermediate oxide and avoiding their agglomeration.
[0044] In some optional embodiments, the platinum salt comprises platinum tetrachloride; and / or,
[0045] The nickel-containing solution includes at least one of nickel chloride, nickel nitrate and nickel sulfate.
[0046] In the embodiments of the present application, the selection of specific platinum salts and nickel-containing solutions is limited, which can include most of the raw materials for preparing platinum and nickel alloy catalysts, thereby improving the preparation method of the present application.
[0047] like Figure 1 As shown, based on a general inventive concept, an embodiment of the present application provides a method for preparing the alloy catalyst, the method comprising:
[0048] S1. Pre-treating the fruit skin, and then heating it under a protective atmosphere until it is carbonized to obtain biomass carbon;
[0049] S2. adding the mixture of the nitride and anhydrous ethanol to the biomass carbon to react to obtain nitrogen quantum dotted biomass carbon;
[0050] S3. adding the platinum salt to the nitrogen quantum dot biomass carbon, and dropping the nickel-containing solution and the sodium ethoxide solution, stirring, and then adding sodium borohydride to the mixture, and reacting to obtain a mixed slurry;
[0051] S4. Dry the mixed slurry, and then calcine it in an oxygen atmosphere to obtain a biomass carbon-based nitrogen quantum dot alloy catalyst.
[0052] In the embodiments of the present application, by carbonizing the surface of fruits and vegetables and utilizing the unique structural structure of the fruit and vegetable skin, a unique ring structure can be formed after carbonization. This ring structure can expose more hydroxyl groups, carboxyl groups and other groups on the surface of biochar and distribute them more evenly, thereby being able to better load platinum and nickel elements, and then preparing platinum and nickel alloy catalysts, thereby being able to effectively improve the aggregation phenomenon of platinum alloy catalysts by nitrogen quantum dotting biomass carbon.
[0053] The method is implemented for the above-mentioned alloy catalyst. The specific composition of the alloy catalyst can refer to the above-mentioned embodiment. Since the method adopts part or all of the technical solutions of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be described one by one here.
[0054] like Figure 2 As shown, in some optional embodiments, the pretreatment of the fruit skin and the subsequent heating under a protective atmosphere to obtain biomass carbon specifically includes:
[0055] S101. Select the melon and fruit skin, cut it, and then soak it in a strong alkaline solvent to obtain the pretreated melon and fruit skin;
[0056] S102. The pretreated fruit skin is heated under a protective atmosphere until carbonized to obtain biomass carbon.
[0057] In the embodiments of the present application, by soaking the cut fruit and melon skins in a strong alkaline solution, on the one hand, the fiber structure on the fruit and melon skins can be stretched out, thereby forming a unique ring structure in the subsequent carbonization stage; on the other hand, the acidic components on the fruit and melon skins are neutralized by a strong alkaline solvent, thereby avoiding the destruction of the ring structure by the acidic components during the carbonization stage.
[0058] In some optional embodiments, the strong alkaline solvent includes potassium hydroxide solution and / or sodium hydroxide solution.
[0059] In the embodiments of the present application, the specific composition of the strong alkaline solvent is controlled to ensure the treatment effect of the strong alkaline solvent on the fruit skin, thereby ensuring that the fruit skin forms a unique ring structure after the carbonization stage.
[0060] In some optional embodiments, the soaking time is ≥ 8 h.
[0061] In the embodiments of the present application, the specific soaking time is controlled to ensure that the fruit skin absorbs enough strong alkaline solvent, which on the one hand ensures the formation of a unique ring structure, and on the other hand can neutralize the acidic impurities in the fruit skin to avoid the destruction of the ring structure by the acidic components during the carbonization process.
[0062] In some optional embodiments, the end temperature of the heating is 600° C. to 900° C.; and / or,
[0063] The calcination temperature is 250°C to 350°C.
[0064] In the embodiments of the present application, the specific heating temperature is controlled to ensure that the skin of fruits and vegetables treated with a strong alkaline solution is carbonized and forms a unique ring structure.
[0065] Controlling the specific temperature of roasting can ensure that the nitrogen quantum dotted biomass carbon loaded with platinum salt and nickel-containing solution fully reacts to form an alloy catalyst with high stability and high activity.
[0066] In some optional embodiments, the heating rate of the calcining is 1.5 to 2.5 times the heating rate of the heating.
[0067] In the embodiments of the present application, the multiple relationship between the heating rate of roasting and the heating rate of heating is controlled. Since the structure of biomass carbon is easy to change, the heating rate of roasting and the heating rate of heating are limited to ensure the structural integrity of the biomass carbon formed on the skin of fruits and vegetables. At the same time, it can also ensure that the nitrogen quantum dotted biomass carbon loaded with platinum salt and nickel-containing solution is fully reacted to form an alloy catalyst with high stability and high activity.
[0068] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0069] Example 1
[0070] The preparation process of alloy catalyst is as follows:
[0071] 1. Preparation of nitrogen quantum dotted biomass carbon: Cut a piece of watermelon, remove the flesh and green peel, cut the obtained white peel into small pieces of 1cm×1cm and put it into a 5% NaOH solution, dry it after leaving it for 4 hours, put it into a muffle furnace for baking, the heating rate is 5℃ / min, heat it to 200℃ and keep it warm for 1h, then continue to heat it to 700℃ at a rate of 5℃ / min, and keep it warm for 1h, take it out after natural cooling, and get biomass carbon. Then weigh 1g of biochar and add it to a beaker, continue to add 0.5g of polyetherimide and 0.5g of 3,4-dihydroxyphenylethylamine and 20g of anhydrous ethanol to the beaker, and stir it at room temperature for 4h to get nitrogen quantum dotted biomass carbon.
[0072] 2. Weigh 1g of nitrogen quantum dotted biomass carbon and put it into a beaker, add 0.1g of platinum tetrachloride and 0.1g of nickel chloride to the beaker, then use anhydrous ethanol as a solvent, add 20mL of anhydrous ethanol, and then add 1g of sodium acetate to adjust the pH, stir and react, and then add 0.2g of sodium borohydride to the solution after 2h of reaction, stir and react for 2h, then dry and take out the solid. The obtained solid is placed in a muffle furnace for baking, the heating rate is 10℃ / min, the temperature is raised to 300℃ and kept for 1h, and then taken out after cooling to obtain an alloy catalyst.
[0073] Example 2
[0074] Comparing Example 2 with Example 1, the difference between Example 2 and Example 1 is:
[0075] The preparation process of alloy catalyst is as follows:
[0076] 1. Preparation of nitrogen quantum dotted biomass carbon: Take a piece of grapefruit peel, peel off the outer yellow part, leaving the white peel, cut the obtained white peel into small pieces of 1cm×1cm and put it into a 5% NaOH solution, dry it after leaving it for 4 hours, put it into a muffle furnace for baking, the heating rate is 5℃ / min, heat it to 200℃ and keep it warm for 1h, then continue to heat it to 700℃ at a rate of 5℃ / min, and keep it warm for 1h, take it out after natural cooling, and get biomass carbon. Then weigh 1g of biochar and add it to a beaker, continue to add 3g of polyetherimide and 3g of 3,4-dihydroxyphenylethylamine and 20g of anhydrous ethanol to the beaker, and stir it at room temperature for 4h to get nitrogen quantum dotted biomass carbon.
[0077] 2. Weigh 1g of nitrogen quantum dotted biomass carbon and put it into a beaker, add 0.2g of platinum tetrachloride and 0.2g of nickel chloride to the beaker, then use anhydrous ethanol as a solvent, add 40mL of anhydrous ethanol, and then add 1g of sodium acetate to adjust the pH, stir and react, and then add 0.4g of sodium borohydride to the solution after 2h of reaction, stir and react for 2h, then dry and take out the solid. The obtained solid is placed in a muffle furnace for baking, the heating rate is 10℃ / min, the temperature is raised to 300℃ and kept for 1h, and then taken out after cooling to obtain an alloy catalyst.
[0078] Example 3
[0079] Comparing Example 3 with Example 1, the difference between Example 3 and Example 1 is:
[0080] The preparation process of alloy catalyst is as follows:
[0081] 1. Preparation of nitrogen quantum dotted biomass carbon: Take a piece of wax gourd peel, peel off the edible flesh inside and the green skin outside, leaving only the white peel in the middle, cut the obtained white peel into small pieces of 1cm×1cm and put it into a 5% NaOH solution, dry it after 4 hours, put it into a muffle furnace for baking, the heating rate is 5℃ / min, heat it to 200℃ and keep it warm for 1h, then continue to heat it to 700℃ at a rate of 5℃ / min, and keep it warm for 1h, take it out after natural cooling, and get biomass carbon. Then weigh 1g of biochar and add it to a beaker, continue to add 5g of polyetherimide and 5g of 3,4-dihydroxyphenylethylamine and 40g of anhydrous ethanol to the beaker, and stir at room temperature for 4h to get nitrogen quantum dotted biomass carbon.
[0082] 2. Weigh 1g of nitrogen quantum dotted biomass carbon and put it into a beaker, add 0.3g of platinum tetrachloride and 0.3g of nickel chloride to the beaker, then use anhydrous ethanol as a solvent, add 40mL of anhydrous ethanol, and then add 1g of sodium acetate to adjust the pH, stir and react, and then add 0.4g of sodium borohydride to the solution after 2h of reaction, stir and react for 2h, then dry and take out the solid. The obtained solid is placed in a muffle furnace for baking, the heating rate is 10℃ / min, the temperature is raised to 300℃ and kept for 1h, and then taken out after cooling to obtain an alloy catalyst.
[0083] Example 4
[0084] Comparing Example 4 with Example 3, the difference between Example 4 and Example 3 is:
[0085] Replace the winter melon rind with watermelon rind and follow the same procedures.
[0086] Comparative Example 1
[0087] Comparative Example 1 and Example 1 are compared. The difference between Comparative Example 1 and Example 1 is:
[0088] The platinum-cobalt alloy catalyst is provided by umicore, and the specific brand number or catalyst model is 0690
[0089] Related experiments and effect data:
[0090] The catalysts of Example 1 and Comparative Example 1 were prepared into catalyst slurries under the same conditions, and the electrochemical active area of the catalyst slurries was tested by the rotating disk electrode method. Then, the slurries were circulated for 1000 times on an electrochemical workstation. After the cycle, the electrochemical active area test was continued. The results are shown in Table 1.
[0091] Table 1 Test results of electrochemical active area of catalysts obtained in Example 1 and Comparative Example 1
[0092]
[0093] It can be seen from Table 1 that:
[0094] After modification with nitrogen quantum dot biomass carbon, the electrochemical active area of the catalyst slurry of Example 1 reached 60.3 m 2 / g, better than 57.2m / g of comparative example 1 2 / g, after running on the rotating disk electrode for 1000 times, the electrochemical active area of the catalyst slurry of Example 1 increased from 60.3m 2 / g dropped to 58.7m 2 / g, the attenuation rate is 2.65%; while the electrochemical active area of the commercial catalyst slurry of Comparative Example 1 is 57.2m 2 / g dropped to 53.4m 2 / g, and the decay rate is 6.64%. This shows that the initial catalytic activity of the biomass carbon alloy catalyst after nitrogen quantum dot is higher, and after running for the same time, the electrochemical active area of the catalyst remains at a high level, showing better durability.
[0095] In summary, the alloy catalyst provided in the present application has a better electrochemical active area than commercial alloy catalysts, and its performance decay rate is also lower after 1000 cycles.
[0096] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0097] In this application, unless otherwise specified, directional words such as "upper" and "lower" used refer specifically to the directions of the drawings in the accompanying drawings. In addition, in the description of the specification of this application, the terms "include", "comprise", etc. mean "including but not limited to".
[0098] In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "multiple" refers to two or more. "At least one", "the following at least one (individual)" or similar expressions refer to any combination of these items, including any combination of single (individual) or plural (individual). For example, "at least one (individual) of a, b, or c", or "at least one (individual) of a, b, and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, wherein a, b, c can be single or multiple respectively.
[0099] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing an alloy catalyst, characterized in that: The method comprises: Pre-treating the fruit skin, and then heating it under a protective atmosphere until it is carbonized to obtain biomass carbon; Adding a mixture of nitride and anhydrous ethanol to the biomass carbon for reaction to obtain nitrogen quantum dotted biomass carbon; Adding platinum salt to the nitrogen quantum dotted biomass carbon, and dropping a nickel solution and a sodium ethoxide solution, stirring, and then adding sodium borohydride to the mixture, and reacting to obtain a mixed slurry; The mixed slurry is dried, and then calcined in an oxygen atmosphere to obtain a nitrogen quantum dot alloy catalyst based on biomass carbon; The mass ratio of the nitrogen quantum dotted biomass carbon, platinum salt, and nickel-containing solution is 1:0.1-0.3:0.1-0.3; The nitride includes a mixture of polyetherimide and 3,4-dihydroxyphenylethylamine.
2. The method according to claim 1, characterized in that: The pretreatment of the fruit skin and the subsequent heating under a protective atmosphere to obtain biomass carbon specifically includes: Selecting fruit skins, cutting them, and then soaking them in a strong alkaline solvent to obtain pretreated fruit skins; The pretreated fruit skin is heated under a protective atmosphere until carbonized to obtain biomass carbon.
3. The method according to claim 2, characterized in that The strong alkaline solvent includes potassium hydroxide solution and / or sodium hydroxide solution.
4. The method according to claim 2, characterized in that: The soaking time is ≥8h.
5. The method according to claim 1, characterized in that The end point temperature of the heating is 600° C. to 900° C.; and / or, The calcination temperature is 250°C to 350°C.
6. The method according to claim 1, characterized in that The heating rate of the calcination is 1.5 to 2.5 times the heating rate of the heating.
7. The method according to claim 1, characterized in that The mass ratio of the biomass carbon to the nitride is 1:1-10.
8. The method according to claim 1, characterized in that: The platinum salt includes platinum tetrachloride; and / or the nickel-containing solution includes at least one of nickel chloride, nickel nitrate and nickel sulfate.
Citation Information
Patent Citations
Preparation method and application of nitrogen-doped carbon supported metal nanoparticles electrocatalyst with uniform particle size for alkaline hydroxidation reaction
CN109103473A
Method for preparing biochar-based oxygen reduction reaction catalyst by using bean dregs and product
CN109841858A
Platinum-based alloy porous nanosphere electrocatalyst with high oxygen reduction performance and preparation method of platinum-based alloy porous nanosphere electrocatalyst
CN114759204A